Supervisi Klinis dalam Pembinaan Profesionalisme Guru MA Amanatulloh Banyuwangi - Aniq Nasikhatul Murtafi’ah; Moh. Harun Al Rosid (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2024)
Clinical supervision is an effort by madrasah heads to develop teachers to become more professional in teaching. Implementation of clinical supervision focuses on improving teacher weaknesses in learning This research aims to describe clinical supervision through planning, classroom observation, and evaluation and analysis in the professional development of teachers at MA Amanatulloh at the Amanatulloh Banyuwangi Islamic Boarding School. This research approach is qualitative with a case study type of research. Data collection techniques include interviews, observation and documentation. The research subjects were the school principal as supervisor, teachers and students. Data analysis through data condensation, data presentation, and drawing conclusions. Test the validity of the data through credibility tests and confirmability tests. To ensure whether the data is valid or not through data source triangulation, method triangulation, and member check. The results of the research are (1) madrasa head planning; stimulus through meetings to share perceptions of clinical supervision goals, problem identification, supervision implementation schedule contracts, instruments, implementation concepts, and teacher problem focus. (2) Class observation; The supervisor and teacher enter the classroom together to make observations regarding the teacher's teaching skills, the teacher's interaction with students, and the feedback from the students themselves. (3) Evaluation and analysis; the process of evaluating and analyzing the results which are used as benchmarks for follow-up activities to improve teachers through discussion and analysis. Supervisors direct teachers to take part in training and be actively involved in MGMP forums to strengthen knowledge and benchmark learning to make it more varied.